Immune checkpoint inhibitors and cellular treatment for lymphoma immunotherapy. (28th March 2021) - Li, F.; Chen, Y.; Pang, M.; Yang, P.; Jing, H.
Summary: Malignant lymphoma (ML) is a common hematological malignancy with many subtypes. Patients with ML usually undergo traditional treatment failure and become relapsed or refractory (R/R) cases. Recently, immunotherapy, such as immune checkpoint inhibitors (ICIs) and cellular treatment, has gradually emerged and used in clinical trials with encouraging achievements for ML treatment, which exerts anti‐tumor activity by blocking the immune evasion of tumor cells and enhancing the attack ability of immune cells. Targets of immune checkpoints include programmed cell death‐1 (PD‐1), programmed cell death‐ligand 1 (PD‐L1), cytotoxic T lymphocyte‐associated protein 4 (CTLA‐4), T cell immunoglobulin and ITIM domain (TIGIT), T cell immunoglobulin‐3 (TIM‐3) and lymphocyte activation gene 3 (LAG‐3). Examples of cellular treatment are chimeric antigen receptor (CAR) T cells, cytokine‐induced killer (CIK) cells and natural killer (NK) cells. This review aimed to present the current progress and future prospects of immunotherapy in lymphoma, with the focus upon ICIs and cellular treatment. Abstract : Most patients with malignant lymphoma inevitably develop into relapsed or refractory (R/R) cases after traditional treatment failure. Immunotherapy, such as immune checkpoint inhibitors (ICIs) and cellular treatment has played roles in ML treatment by blocking the immune evasion of tumor cells and enhancing the attack ability of immune cells. This review was aimed to present the current progress and future prospects of immunotherapy in lymphoma, with the focus on ICIs and cellular treatment.